The Effect of Family Harmony on Family Business Succession - Salwa Salsabila Aulia Rahmani; Repita Dewi; Septia Pintanawati; Mira Nurfitriya; Azizah Fauziyah (UM Purwokerto Press, 2024)
The succession process certainly has an important impact on the sustainability of the family business. However, in the process there are several obstacles caused by friction on harmony between family members in a family business. The purpose of this study is to determine the description of family harmony and succession in several family business companies, and to find out how much influence family harmony has on succession in a family business. The object of this research includes three family businesses which are Azka Loundry, Payung Geulis and Kelom Geulis. This research uses a quantitative method with a descriptive verification approach. Quantitative data were obtained using linear regression techniques. The population of this study was 35 people. This study uses a saturated sample where the population size is the same as the sample size. Estimated results in this study indicate that family harmony has a positive influence on family business succession. This research also provides insight into maintaining family harmony to achieve successful succession in the family business.